Statistical analysis of polycyclic aromatic hydrocarbons concentrations at Baghdad city - M. Almousawi, Israa; H. Mathkor, Thikra; A. Salih, Aessa; H. Afaj, Adnan; A.A.Shanshal, Muthna (Al-Qadisiyah Journal of Pure Science, 2018)
The concentrations of 16 polycyclic aromatic hydrocarbons (PAHs) were determined in aerosol samples, which collected for the period (April 2012 to February 2013) at three sites in Baghdad city (AL-Daura refinery, AL-Daura power plant and thermal power plant South of Baghdad). These aerosol samples undergone soxhlet extraction. After the extraction, 138 samples were analyzed by GC-MS to determine sixteen PAH compounds. The average concentrations of individual PAHs were measured in ambient air at the various season. The results indicate the spread of most of the sixteen PAHs at three sites in Baghdad city. Effect of sampling locations, seasons and meteorological conditions on the concentrations of PAHs were studied by SPSS. The positive correlation between the temperature and the total PAH concentration was varied in seasons, which indicated the existence of extrusive relationship between temperature and the total polycyclic aromatic hydrocarbon (TPAH) in the chosen sites.